الخدمات السياحية وإدارة الانطباع عبر تطبيقات الهواتف الذكية تطبيق Tripadvisor دراسة حالة - نومار مريم نريمان; ملوكي عبد الله (المجلة الجزائرية للأمن الإنساني, 2023)
The tourism sector is witnessing intense competition developments, especially with the recent technological revolution, where customers search for and book travel services via the Internet, which prompts tourism companies to permanently develop their services in line with customers’ needs. By applying the concepts of Goffman’s dramaturgy and impression management on smartphone applications, we seek through this study to reveal the methods of impression management about various tourism services through smartphone applications. A case study of the TripAdvisor application; Which is considered one of the most prominent sites that millions of tourists rely on for their tourist destinations. With the aim of identifying recent trends in impression management; the importance of this study is demonstrated by highlighting the typographical elements in the TripAdvisor application that will manage the impression of customers, help them make decisions, and accompany them during their tours.